2009
DOI: 10.1111/j.1399-0004.2009.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

SMARCB1/INI1 maternal germ line mosaicism in schwannomatosis

Abstract: Schwannomatosis is characterized by the development of multiple schwannomas of the nervous system, but without the occurrence of vestibular schwannomas. Most cases of schwannomatosis are thought to be sporadic, representing the first case in a family due to a new mutation in the causative gene. We recently identified SMARCB1/INI1 as a schwannomatosis-predisposing gene. Here, we analyzed this gene in a schwannomatosis family with two affected children, but with clinically unaffected parents. Both affected indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Indeed, splice sites mutations are predominantly observed in schwannomatosis (12/20 reported; refs. [21][22][23][24]27), whereas they are rare in RTs and particularly associated with asymptomatic carriers (3/5 heritable mutations of hSFN5/INI1; refs. 7,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, splice sites mutations are predominantly observed in schwannomatosis (12/20 reported; refs. [21][22][23][24]27), whereas they are rare in RTs and particularly associated with asymptomatic carriers (3/5 heritable mutations of hSFN5/INI1; refs. 7,14).…”
Section: Discussionmentioning
confidence: 99%
“…1). Secondly, as germline hSNF5/INI1 mutation is known to predispose not only to early aggressive RTs with rapid fatal outcome but also to late-onset indolent multiple schwannomas (21)(22)(23)(24)(25)(26)(27) and meningiomas (21,28), predicting the outcome of a mutation carrier seems somewhat hazardous. Indeed, different tumor types may selectively affect the members of a family carrying the same mutation in a so far unpredictable manner (26).…”
Section: Discussionmentioning
confidence: 99%
“…13 Germline SMARCB1 alterations also appear to underlie schwannomatosis. [47][48][49] Very rare instances of MRT and epithelioid MPNST arising in schwannomatosis have been reported, presumably reflecting second somatic mutations. 50,51 Epithelioid malignant peripheral nerve sheath tumor Malignant peripheral nerve sheath tumors are relatively rare, accounting for roughly 5% of all soft tissue sarcomas.…”
Section: Smarcb1 (Ini1 Snf5 Baf47)mentioning
confidence: 99%
“…Moreover, we unexpectedly observed some features compatible with benign nervous proliferation within or near the rhabdoid components. Given the recent works showing the links between SMARCB1 germline mutations, acquired NF2 somatic inactivation in Schwann cells, and development of schwannomas, 9,11,20,25,26,35,37,39 a potential genetic relationship between common PNS tumors-that is, neurofibromas, schwannomas, and MPNST-and our cases actually required further investigation. Although NF2 constituted an attractive candidate gene, we found only 3 hemizygous deletions and no mutation.…”
Section: Discussionmentioning
confidence: 83%
“…24 Strikingly, recent studies also showed that SMARCB1 germline mutations are the underlying cause of a subset of familial and sporadic schwannomatosis and rare forms of familial meningiomas. 9,11,20,25,26,35,37,39 Schwannomatosis is a genetic disorder characterized by the development of multiple schwannomas in the fourth to fifth decade of life. The occurrence of both RT and schwannomas within families with a unique SMARCB1 germline mutation confirms that a common genetic disorder could be shared by these 2 types of tumors.…”
mentioning
confidence: 99%